Exploiting Trap Type and Color for Monitoring Macadamia Felted Coccid Acanthococcus ironsidei (Williams) and Associated Parasitic Wasps in Macadamia Orchards in Hawai’i - Angelita L. Acebes-Doria; Pascal O. Aigbedion-Atalor (Insects)
Acanthococcus ironsidei (Williams) (Hemiptera: Eriococcidae) is an invasive pest of macadamia, Macadamia integrifolia, in Hawai’i, causing death to macadamia trees and decreased nut productivity. Monitoring relies on wrapping double-sided sticky tapes over tree branches to trap dispersing crawlers (i.e., mobile immature stage), but this is tedious for growers, especially in large orchards. From September to November 2022 and December 2022 to February 2023, at two commercial macadamia orchards on Hawai’i Island, the use of colored sticky cards was assessed for improving the monitoring of A. ironsidei and to investigate the Hymenopteran parasitoid complex that inhabits macadamia canopies. At each study site, four different colored sticky cards (yellow, lime green, dark green, and white) were placed on the lower canopy of five trees, and on each tree, a transparent double-sided sticky tape was deployed. At bi-weekly intervals, the sticky cards were replaced and re-randomized on each tree, and the double-sided sticky tapes were replaced. The results showed that the sticky cards captured both A. ironsidei crawlers and (winged) male adults, while the double-sided sticky tapes captured only crawlers. The trap color did not have significant effects on the captures of A. ironsidei male adults at the sites, while the captures of crawlers on sticky cards were lowest on the dark green sticky traps at one site. The captures of A. ironsidei adult males on white sticky traps were generally correlated with the number of crawlers captured on the double-sided sticky tapes. The parasitoid complex captured had disparities in the attraction to color; however, the yellow, lime green and dark green colors were seemingly more effective for monitoring Encarsia lounsburyi (Berlese & Paoli), a reported parasitoid of A. ironsidei. These results have useful practical implications for improved monitoring of A. ironsidei crawlers, male adults and associated natural enemies.